Plan de negocio para la creación de una aplicación móvil enfocada a la organización de partidos de fútbol amateur en la ciudad de Quito, tomando las mejores prácticas internacionales de España - Basurto López, Jhuliana Belén (2019)
Over the last years, in Ecuador and in the entire world, the technology of communication and information have considerably influenced in the development of several industries. Nowadays, mobile applications are booming in the market facilitating the life of consumers and providing helpful tools for their daily life. Nevertheless, in Ecuador the apps that have great reception and the ones that are pioneers are international franchises that have invested mostly in the transport and delivery setting. For this reason, the present project proposes the idea of developing a local app taking the best practices of foreign companies expertise in this business model, through the analysis and comparison of three different companies located in different countries and that have been successful in environments highly influenced by the soccer culture. One example is Spain, a country not only prominent in soccer but also in the technological development, that thanks to the creation of these mobiles apps has generated considerable profitability offering a tool that connects players, organizers and synthetic fields. On the other hand, after carrying out the evaluation of the project, the market research was able to determine that both the final users and the synthetic courts would be willing to be part of the project. At least 165453 users will benefit from this tool and 58 synthetic courts would be the sports centers where the games will be carried out. Finally, it can be mentioned that the NPV is positive, the IRR is higher than the interest rate and the recovery period is approximately 3 years, which shows that the project is viable.